Method for preparing negative carbon cement soil through corn straw biochar synergistic carbonization curing technology

By using corn stalk biochar collaborative carbonization maintenance technology in cement soil, the problem of insufficient carbon emissions and strength in modified materials is solved, and efficient carbonization and strength improvement is achieved, meeting the roadbed of expressways and first-class highways Material requirements.

CN119390392APending Publication Date: 2025-02-07SHAOXING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411297610.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing cement soil has problems such as increasing carbon emissions, increasing soil alkalinity and serious natural resource consumption in modified materials, and it is difficult to effectively improve the strength and carbonization effect of cement soil.

Method used

The original composite material is prepared by mixing soft soil, cement, corn stalk biochar and water in proportion, and then the modified cement soil is obtained by compacting and demolding multiple times. Carbonization curing is carried out to obtain negative carbohydrate cement soil.

Benefits of technology

It effectively improves the unbounded compressive strength (UCS) of cement soil, enhances the carbonization effect of cement soil, reduces CO2 emissions, and improves the cementitiousness, compactness and carbon sequestration ability of cement soil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390392A_ABST
    Figure CN119390392A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing negative carbon cement soil by a corn straw biochar synergistic carbonization curing technology, which comprises the following steps: (1) preparing an undisturbed composite material: uniformly stirring and mixing soft soil, cement, corn straw biochar and water in proportion to obtain the undisturbed composite material; (2) preparing modified cement soil: adding the original composite material into a mold for multiple times, compacting and demolding to obtain the modified cement soil; and (3) curing: performing carbonization curing on the modified cement soil to obtain the negative carbon cement soil. According to the method, the strength of the cement soil can be effectively improved, the carbonization effect of the cement soil is enhanced, carbon neutralization of building materials can be achieved, and support is provided for achieving the ambitious goal of carbon reaching the peak.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cement soil preparation, and more specifically, to a method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization and curing technology. Background Art

[0002] Soft soil is mainly distributed in coastal areas around the world. Due to its poor engineering properties such as high water content, large pores and low strength, it is extremely unfavorable for local engineering construction. With the acceleration of urbanization, some infrastructure and civil buildings have begun to be built in coastal areas in large numbers. However, when the soft soil foundation is subjected to the load of the upper structure, it may undergo uneven settlement due to insufficient bearing capacity, resulting in engineering problems such as instability or collapse of the upper overall structure. In view of this, the use of admixtures such as cement and lime to reinforce and stabilize soft soil to improve its mechanical properties is a common and easy treatment method in the industry. However, the large-scale use of cement and lime leads to a series of environmental problems such as increased carbon emissions, increased soil alkalinity, and serious consumption of natural resources. According to statistics, the amount of CO2 emitted by cement production accounts for 8% of the total global CO2 emissions. It is estimated that the total amount of CO2 emitted by cement production will be close to 4.7 billion tons in 2030. Therefore, it is an urgent problem to seek green, low-carbon and environmentally friendly admixtures to reduce the demand and dependence on cement, reduce CO2 emissions, and improve the mechanical properties of cement soil modified materials. Summary of the invention

[0003] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization curing technology, which can effectively improve the strength of cement soil, enhance the carbonization effect of cement soil, and has good practical application value.

[0004] In order to achieve the above object, the present invention adopts the following technical solution:

[0005] A method for preparing negative carbon cement soil using corn straw biochar synergistic carbonization curing technology comprises the following steps:

[0006] (1) Preparing an original composite material: mixing soft soil, cement, corn straw biochar, and water in a certain proportion to obtain an original composite material;

[0007] (2) preparing modified cement soil: adding the original composite material into a mold in multiple times, compacting, and demolding to obtain modified cement soil;

[0008] (3) Curing: The modified cement soil is subjected to carbonization curing to obtain negative carbon cement soil.

[0009] Furthermore, the moisture content of the original composite material is 20%.

[0010] Furthermore, in the original composite material, cement accounts for 5% of the mass of the soft soil.

[0011] Furthermore, corn stover biochar accounts for 3-7% of the total mass of cement and soft soil.

[0012] Furthermore, the modified cement soil is subjected to standard curing or no standard curing before carbonization curing; if no standard curing is performed or the standard curing age is less than 7 days, the carbonization curing conditions are: temperature of 18-22°C, humidity of 70%, CO2 concentration of 50%, and carbonization time of 5-15 hours; if the standard curing age is greater than or equal to 7 days, the carbonization curing conditions are: temperature of 18-22°C, humidity of 70%, CO2 concentration of 50%, and carbonization time of less than or equal to 10 hours.

[0013] Furthermore, standard curing conditions are: temperature of 18-22°C and humidity of 95%.

[0014] Furthermore, the specific preparation steps of the original composite material are: after the soft soil and cement are mixed and stirred evenly, the corn straw biochar is poured in and stirred and mixed again, and then water is added and stirred and mixed again to obtain the original composite material.

[0015] When the negative carbon cement soil was prepared according to the conditions of 20% moisture content of the original composite material, 5% cement mass of soft soil, 3% corn straw biochar mass of cement and soft soil, and carbonization and curing for 15 hours at 18-22°C, 70% humidity, and 50% CO2 concentration, the CO2 absorption capacity of each ton of the negative carbon cement soil was 33.6kg;

[0016] When negative carbon cement soil is prepared according to the conditions that the moisture content of the original composite material is 20%, cement accounts for 5% of the mass of soft soil, corn straw biochar accounts for 5% of the total mass of cement and soft soil, and carbonization curing is carried out for 15 hours at 18-22°C, humidity 70%, and CO2 concentration of 50%, the CO2 absorption capacity of each ton of the obtained negative carbon cement soil is 38.6kg.

[0017] Furthermore, the unconfined compressive strength UCS of the prepared negative carbon cement soil is calculated using the model formula z = α + βx 1.5 +λlny represents; z represents UCS, kPa; x represents biochar content, %; y represents curing age, h; α, β and λ are the unknown model fitting parameters.

[0018] Furthermore, the unconfined compressive strength of the negative carbon cement soil prepared under the conditions that the moisture content of the original composite material is 20%, the cement accounts for 5% of the soft soil mass, and the corn straw biochar accounts for 5% of the total mass of cement and soft soil and after carbonization curing is higher than 2MPa. The unconfined compressive strength of the negative carbon cement soil prepared under the conditions that the moisture content of the original composite material is 20%, the cement accounts for 5% of the soft soil mass, and the corn straw biochar accounts for 7% of the total mass of cement and soft soil and after carbonization curing is higher than 2MPa, which can meet the requirements of the subbase of expressways and first-class medium and light traffic roads, as well as second-class and below heavy, medium and light traffic highways.

[0019] The beneficial effects of the present invention are:

[0020] The present invention uses corn straw biochar (CS-Biochar) and carbonization technology to prepare cement soil. The addition of CS-Biochar not only improves the UCS (unconfined compressive strength) of the cement soil, but also can effectively promote the adsorption and fixation of CO2 on the surface of the material, thereby enhancing the carbonization effect of the cement soil; carbonization curing further enhances the UCS of the negative carbon cement soil; at the same time, CS-Biochar promotes the cement hydration reaction, and part of the cement hydration products participate in the carbonization reaction, giving play to the synergistic effect of biochar and carbonization technology, thereby further improving the cement soil particle interface bonding force, density and carbon sequestration capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the raw material soft soil used in the present invention;

[0022] Figure 2 This is a SEM image of the raw material corn straw biochar used in the present invention;

[0023] Figure 3 The UCS test result diagram of negative carbon cement soil (i.e., Comparative Examples 1 to Comparative Examples 20) prepared under standard curing conditions;

[0024] Figure 4 The UCS test result diagram of the negative carbon cement soil (i.e., Example 1 to Example 20) prepared under carbonization curing conditions;

[0025] Figure 5 Schematic diagram of the effect of corn straw biochar on cement hydration;

[0026] Figure 6 It is a fitting diagram of the UCS value test results of the CSBCS samples prepared in Example 1 to Example 20 and Comparative Example 1 to Comparative Example 20;

[0027] Figure 7 Schematic diagram of the temperature-increasing decomposition of CSBCS sample;

[0028] Figure 8 TG curves of the CSBCS samples obtained in Examples 1 to 3, 6 to 8, 11 to 13, and 16 to 18;

[0029] Fig. 9 DTG curves of the CSBCS samples obtained in Examples 1 to 3, 6 to 8, 11 to 13, and 16 to 18;

[0030] Fig.10 is the relative carbon fixation amount of the CSBCS samples (i.e., prepared in Examples 1 to 3, 6 to 8, 11 to 13, and 16 to 18) under carbonization curing conditions;

[0031] Fig.11 Schematic diagram of the carbonization reaction mechanism of modified cement soil;

[0032] Fig.12 It is a trend chart of the CO2 absorption amount of 1 ton of CBSCS samples (i.e., prepared by Examples 1 to 3, 6 to 8, 11 to 13, and 16 to 18) and the CO2 amount generated by cement in the 1 ton of CBSCS samples;

[0033] Fig.13 XRD patterns of carbonized and uncarbonized CSBCS samples (i.e., samples obtained from Example 5 and Comparative Example 5, Example 10 and Comparative Example 10, Example 15 and Comparative Example 15, and Example 20 and Comparative Example 50) at 28 days of age;

[0034] Fig.14 The SEM images of CSBCS samples at the age of 28 days after standard curing were magnified 500 times and 5000 times (wherein, Figure (a) is a SEM image of the sample obtained in Comparative Example 5 magnified 500 times, Figure (b) is a SEM image of the sample obtained in Comparative Example 10 magnified 500 times, Figure (c) is a SEM image of the sample obtained in Comparative Example 15 magnified 500 times, Figure (d) is a SEM image of the sample obtained in Comparative Example 20 magnified 500 times, Figure (e) is a SEM image of the sample obtained in Comparative Example 5 magnified 5000 times, and Figure (f) is a SEM image of the sample obtained in Comparative Example 10 magnified 5000 times);

[0035] Fig.15The SEM images are 500 times and 2000 times magnified images of CSBCS samples after carbonization curing for 28 days (wherein, Figure (a) is a 500 times magnified SEM image of the sample obtained in Example 5, Figure (b) is a 500 times magnified SEM image of the sample obtained in Example 10, Figure (c) is a 2000 times magnified SEM image of the sample obtained in Example 5, and Figure (d) is a 2000 times magnified SEM image of the sample obtained in Example 10). DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization curing technology of the present invention comprises the following steps:

[0038] (1) Preparation of undisturbed composite material: soft soil, cement, corn straw biochar (CS-Biochar), and water are mixed in proportion to obtain an undisturbed composite material; the moisture content of the undisturbed composite material is 20%; the cement accounts for 5% of the mass of the soft soil, and the corn straw biochar accounts for 3-7% of the total mass of the cement and the soft soil.

[0039] The specific preparation steps are: mix the soft soil and cement in a mixer and stir evenly, pour in the corn straw biochar and stir again, then add water and continue to stir.

[0040] (2) preparing modified cement soil: adding the original composite material into a mold in multiple times, compacting, and demolding to obtain modified cement soil;

[0041] (3) Curing: Carbonization curing is performed on the modified cement soil to obtain negative carbon cement soil; before carbonization curing, the modified cement soil is subjected to standard curing or no standard curing; if no standard curing is performed or the standard curing age is less than 7 days, the carbonization curing conditions are: temperature 18-22°C, humidity 70%, CO2 concentration 50%, and carbonization time 5-15 hours; if the standard curing age is greater than or equal to 7 days, the carbonization curing conditions are: temperature 18-22°C, humidity 70%, CO2 concentration 50%, and carbonization time less than or equal to 10 hours. The standard curing conditions are: temperature 18-22°C, humidity 95%.

[0042] In the present invention, the soft soil used is yellow-brown after drying, and its SEM is as follows: Figure 1Corn straw biochar (CS-Biochar) was obtained from Shengxiang Activated Carbon Business Department in Gongyi City, Henan Province, and is in the form of black powder; CS-Biochar has a rough surface and a porous structure. Compared with rice straw biochar, it has higher stability and CO2 adsorption capacity. Its SEM is shown in Figure 2 As shown in the figure, PO42.5 silicate cement is used.

[0043] The specific embodiments are as follows:

[0044] Example 1-Example 20

[0045] Negative carbon cement soil was prepared according to the raw materials and conditions shown in Table 1. The specific steps are as follows:

[0046] (1) Soft soil and cement were mixed in a mixer for 5 min, corn straw biochar was added and stirred for another 5 min, and then water was added and stirred for another 10 min to obtain the original composite material.

[0047] (2) The original composite material was added into a cylindrical metal mold with a height of 80 mm and a diameter of 39.1 mm in three times, compacted with a hydraulic jack, and demolded after standing for 5 minutes to obtain a cylindrical modified cement soil;

[0048] (3) Curing: The modified cement soil was subjected to standard curing or not at a temperature of 18-22°C and a humidity of 95%, and carbonization curing was performed at a temperature of 18-22°C, a humidity of 70%, and a CO2 concentration of 50% to obtain negative carbon cement soil. The prepared negative carbon cement soil samples were uniformly numbered as carbonization-cured CSBCS-X, where X represents the percentage content of CS-Biochar in the total mass of cement and soft soil.

[0049] Table 1

[0050]

[0051]

[0052] Comparative Example 1-Comparative Example 20

[0053] Negative carbon cement soil was prepared according to the raw materials and conditions shown in Table 2. The specific steps are as follows:

[0054] (1) Soft soil and cement were mixed in a mixer for 5 min, corn straw biochar was added and stirred for another 5 min, and then water was added and stirred for another 10 min to obtain the original composite material.

[0055] (2) The original composite material was added into a cylindrical metal mold with a height of 80 mm and a diameter of 39.1 mm in three times, compacted with a hydraulic jack, and demolded after standing for 5 minutes to obtain a cylindrical modified cement soil;

[0056] (3) Curing: The modified cement soil was subjected to standard curing at a temperature of 18-22°C and a humidity of 95% to obtain negative carbon cement soil. The prepared negative carbon cement soil samples were uniformly numbered as uncarbonized cured CSBCS-X, where X represents the percentage content of CS-Biochar in the total mass of cement and soft soil.

[0057] Table 2

[0058]

[0059]

[0060] Results and Discussion

[0061] (1) Unconfined compressive strength (UCS)

[0062] UCS test method: The LDF UCS tester is used to test the specimens after reaching the set curing conditions. The test loading rate is 1mm / min, and the data collection time interval is 2s. The UCS tester can apply a maximum axial load of 10kN, and the specimen is a cylinder with a diameter of 39.1mm and a height of 80mm.

[0063] The UCS of negative carbon cement soil prepared under different curing conditions (i.e., carbonized and cured CSBCS samples prepared in Examples 1 to 20 and uncarbonized and cured CSBCS samples prepared in Comparative Examples 1 to 20) are as follows: Figure 3 , Figure 4 shown.

[0064] Figure 3 It shows that under standard curing conditions, as the percentage of CS-Biochar in the total mass of cement and soft soil (hereinafter referred to as "CS-Biochar content") increases, the UCS of the uncarbonized cured CSBCS sample tends to gradually increase. When the CS-Biochar content is 7%, the UCS reaches the maximum value. Compared with the uncarbonized cured CSBSC-0 sample, the UCS of the uncarbonized cured CSBCS-7 sample increased by 46% (5h), 70% (10h), 45% (15h), 35% (7d) and 26% (28d), respectively.

[0065] Under carbonization curing conditions, the variation pattern of UCS of carbonization cured CSBCS samples with increasing CS-Biochar content is the same as that under standard curing conditions, e.g. Figure 4As shown, carbonization curing is more conducive to the development of UCS. The study found that the UCS of the carbonized CSBCS-7 sample increased by 42% (5h), 80% (10h), 77% (15h), 17% (7d) and 22% (28d) respectively compared with the uncarbonized CSBCS-7 sample. This is because the silica gel and calcium carbonate generated by the carbonization reaction can cement the soil particles and fill the pores between the soil particles, enhance the close connection between the soil particles, and thus improve the strength of the carbonized sample. In the first 10 hours of carbonization, the growth rate of UCS is fast, and then gradually slows down with the increase of carbonization time. This is because as the carbonization time increases, the sample gradually becomes denser and the pores decrease, making it more difficult for carbon dioxide to enter the interior of the sample, so the growth rate of strength gradually slows down.

[0066] The characteristics of biochar play a key role in improving UCS. First, biochar can absorb free water in the internal pores of the sample, avoiding the evaporation of some water. Second, the filling effect of biochar promotes the densification of the internal structure of cement. At the same time, the negatively charged functional groups on the surface of biochar attract the surrounding positively charged hydrated cement particles and provide them with nucleation sites, resulting in nucleation clusters. In addition, the wet surface and macroporous structure of biochar also provide favorable conditions for the generation and growth of hydration products. Figure 5 Schematic diagram showing the effect of biochar on cement hydration.

[0067] Obviously, age plays a positive role in the UCS of cement soil. Under standard curing conditions, the UCS of the samples cured for 28 days increased by 1.76 times, 1.55 times, 1.53 times and 1.39 times respectively compared with the samples cured for 5 hours in the samples with the same CS-Biochar content. At the same time, the UCS of the carbonized and cured CSBCS samples with the same CS-Biochar content and the uncarbonized CSBCS samples were compared. The UCS of the carbonized and cured 7-day-old samples was basically equivalent to the UCS of the standard cured 28-day-old samples. It can be seen that carbonization is conducive to the improvement of the early strength of negative carbon cement soil, thereby shortening the construction period.

[0068] Through the above analysis of UCS of negative carbon cement soil samples, it was found that there is a strong correlation between UCS and CS-Biochar content and curing age (C). In order to better characterize the relationship between the three, a prediction model for UCS is proposed, as shown in formula (1):

[0069] z=α+βx 1.5 +λlny (1)

[0070] Where z represents UCS, kPa; x represents CS-Biocha content, %; y represents curing age, h; α, β and λ are fitting parameters.

[0071] In order to verify the applicability of formula (1), the UCS values ​​of CSBCS samples (including carbonized CSBCS samples and uncarbonized CSBCS samples) were fitted. The results are shown in Figure 6 As shown in the figure, the predicted value of UCS is basically consistent with the measured value. Under standard curing conditions, the corresponding fitting parameters α, β, and λ are 116, 23.3, and 251 respectively, and the correlation coefficient R 2 It is 0.990, indicating that formula (1) can better capture the relationship between UCS, CS-Biochar and curing age, which can provide a theoretical basis for the application of CS-Biochar (content 0% to 7%) in cement soil.

[0072] According to the 7d age UCS standard R for cement stabilized materials in the specification JTG / TF20-2015 d According to the regulations, the UCS of the uncarbonized CSBCS samples is lower than 2MPa, which is only suitable for the subbase of medium and light traffic roads of level II and below. However, the samples with CS-Biochar content of 5% and 7% have UCS higher than 2MPa after carbonization, which can meet the requirements of the subbase of medium and light traffic roads of expressways and level I highways, as well as the requirements of the subbase of heavy, medium and light traffic roads of level II and below. At the same time, they can also meet the requirements of the subbase of medium and light traffic roads of level II and below. Therefore, carbonization has greatly broadened the application scope of biochar cement soil in highway subgrade.

[0073] (2) Carbon fixation

[0074] In order to explore the influence of CS-Biochar content and carbonization time on the carbon fixation of CSBCS samples, the thermogravimetric analysis method was used for testing. The thermogravimetric analysis method is: using a DSC1 type synchronous thermal analyzer to perform thermogravimetric analysis (TGA) tests on CSBCS samples (i.e., negative carbon cement soil prepared in Examples 1-3, 6-8, 11-13, 16-16) after carbonization for 5h, 10h and 15h respectively; before the test, the samples destroyed in the UCS test were freeze-dried for 24h to prevent further hydration reaction of the samples; then the samples were ground into powder and put into a small crucible and put into a synchronous thermal analyzer for testing; the test temperature range was set to 25℃~900℃, and the heating rate was 20℃ / min.

[0075] Figure 7The schematic diagram of the temperature-increasing decomposition of the CSBCS sample is shown. The figure shows that the decomposition of the hydration and carbonization products of the CSBCS sample is mainly divided into three stages. The temperature between 25℃-200℃ is the first stage, which corresponds to the decomposition of the bound water of the CSH gel; the temperature between 400℃-550℃ is the second stage, which corresponds to the decomposition of Ca(OH)2; the temperature between 550℃-900℃ is the third stage, which corresponds to the decomposition of CaCO3. Among them, under the condition of temperature of 550℃-720℃, the carbonization of CSH gel produces the decomposition of CaCO3 with poor crystallinity. When the temperature reaches 700℃-900℃, the CaCO3 with good crystallinity decomposes. The thermal decomposition of the hydration and carbonization products is shown in the TG curve ( Figure 8 ) on the decreasing and TG derivative curve (DTG curve) ( Fig. 9 ) on the endothermic peak. Therefore, the calculation method of carbon fixation can be expressed as:

[0076]

[0077] Where, CO2uptake is the relative carbon fixation of the sample, %; m 550 and m 900 are the masses of the test sample at 550℃ and 900℃, mg respectively; m0 is the initial mass of the test sample, mg.

[0078] Fig.10 The relative carbon fixation of CSBCS samples under carbonization curing conditions is shown. The figure shows that the relative carbon fixation of the samples increases first and then decreases with the increase of CS-Biochar content. Compared with the carbonization-cured CBSCS-0 sample, the relative carbon fixation of carbonization-cured CSBCS-3, 5, and 7 samples increased by 28% to 44% (5h), 17% to 26% (10h), and 12% to 73% (15h), respectively. Therefore, the addition of biochar not only provides space for the generation of carbonization products, but also strengthens the fixation of CO2 through chemical adsorption, thereby enhancing the carbonization effect of cement soil. This mechanism has a positive effect on improving the carbonization rate and carbonization depth of cement-based materials, and also provides a theoretical basis for using biochar to improve the performance of cement soil.

[0079] The reason why the relative carbon fixation increases first and then decreases with the biochar content is that the excessive biochar content accelerates the carbonization reaction and hydration reaction, generates more calcium carbonate and accumulates in the surface pores, fills the large pores or divides them into small pores, making it more difficult for CO2 to enter the sample. In addition, under the same biochar content, the relative carbon fixation of the sample increases with the increase of carbonization time, and the carbonization-cured CSBCS-0, 3, 5, and 7 samples increase by 8%-28% (C5h~C10h) and 7%-61% (C10h~C15h). And the carbon fixation growth rate of the carbonization-cured CSBCS-3 and 5 samples is significantly better than that of CSBCS-0 and 7.

[0080] According to statistics, the production of 1 ton of cement will produce about 800kgCO2. In order to study how much CO2 absorption of 1 ton of CBSCS sample can offset the amount of CO2 produced by cement in 1 ton of CBSCS sample, the carbonation depth of the sample is calculated. Fig.11 The specific calculation method is shown in formulas (4), (5), (6) and (7):

[0081]

[0082]

[0083]

[0084]

[0085] Where: is the CO2 absorption capacity of 1 ton of CSBCS sample, kg; m CA is the mass of carbonized area of ​​1 ton CSBCS sample, kg; CO2uptake is the relative carbon fixation amount of CSBCS sample, %; V CA is the carbonization area volume of CSBCS sample, cm 3 ; V S is the volume of CSBCS sample, cm 3 ; l CD is the carbonization depth of CSBCS sample, cm; r S is the radius of the CSBCS sample, cm; h S is the height of CSBCS sample, cm.

[0086] Fig.12The variation trend of CO2 absorption of 1 ton CBSCS sample and CO2 produced by cement in 1 ton CBSCS sample is shown. With the increase of CS-Biochar content, CO2 absorption increases first and then decreases; with the increase of carbonization time, CO2 absorption also increases. After carbonization for 5 hours, CO2 absorption of modified cement soil sample offsets 18% to 40% of CO2 produced by cement; after carbonization for 10 hours, CO2 absorption offsets 26% to 64%; after carbonization for 15 hours, CO2 absorption offsets 37% to 127%. CO2 absorption of 1 ton CSBCS-3 sample and CSBCS-5 sample carbonized for 15 hours is 33.6kg and 38.6kg respectively, which can completely offset 31.2kg and 30.4kg of CO2 produced by cement in CSBCS-3 and CSBCS-5 samples, and can also absorb 2.4kg and 8.2kg more CO2 respectively. When the net carbon emission is negative, the CO2 absorption is greater than the emission, and a negative carbon state is reached. If only the CO2 emission during cement production is considered, the negative carbon cement soil prepared by biochar co-carbonization technology is feasible as a roadbed material in road construction. This shows that carbonizing modified cement soil helps achieve "carbon neutrality" of building materials and also provides support for achieving the ambitious goal of "carbon peak".

[0087] (3) Microscopic test (3.1) XRD test

[0088] Under carbonization curing conditions, the substances involved in the carbonization reaction of CSBCS samples include tricalcium silicate (C3S), dicalcium silicate (C2S), calcium hydroxide (CH) and hydrated calcium silicate gel (CSH), and C3S and C2S become the main reactants of the carbonization reaction due to their high carbonization activity. When C3S and C2S undergo hydration reaction, the generated CH and CSH further react with CO2 to generate calcium carbonate (CaCO3) and other carbonization products. At the same time, the addition of biochar promotes the cement hydration reaction, and the generated hydration products accelerate the dissolution of CO2, increasing the ability of cementitious materials to store and absorb CO2. This process not only enhances the strength of the sample, but also helps to fix CO2 in the atmosphere and reduce the impact of the construction industry on the climate and environment. The carbonization reaction formula is as follows.

[0089] C3S+(3-x)CO2+yH2O→C x SH y +(3-x)CaCO3 (8)

[0090] C2S+(2-x)CO2+yH2O→C x SH y +(2-x)CaCO3 (9)

[0091] Ca(OH)2+CO2→CaCO3+H2O (10)

[0092] xCaO·ySiO2·zH2O+xCO2→xCaCO3+y(SiO2·tH2O)+(z-yt)H2O (11)

[0093] The carbonization reaction of CO2 and silicate minerals first produces CSH and CaCO3, and then CSH further reacts with CO2 to produce silica gel polymer (SiO2·H2O) and CaCO3. However, the CSH produced by carbonization has a higher degree of polymerization than the CSH produced by cement hydration. The combined carbon fixation process and carbonization reaction mechanism are as follows: Fig.12 shown.

[0094] Fig.13 The XRD spectra of carbonized and uncarbonized CSBCS samples at 28d age are shown. According to the spectra, the phases of the uncarbonized sample mainly include quartz (SiO2) and CH. The phases of the carbonized sample mainly include quartz (SiO2), CH and CaCO3. Comparing the XRD spectra of the uncarbonized sample with the carbonized sample, it was found that the CH diffraction peak at 17.8° of the uncarbonized sample was significantly higher than that of the carbonized sample. At the same time, a new CaCO3 diffraction peak appeared at 29.3° in the carbonized sample, indicating that CH generated CaCO3 through carbonization reaction. In addition, the CH diffraction peak at 17.8° and the CaCO3 diffraction peak at 29.3° of the CSBCS sample were compared, and it was found that with the increase of CS-Biochar content, the intensities of CH and CaCO3 diffraction peaks first increased and then decreased, among which the diffraction peak intensities of the CSBCS-3 sample at 17.8° and 29.3° were both the largest. In addition, the SEM image shows that CSH gel exists in the sample, but since CSH is an amorphous gel, the sample XRD cannot detect CSH. However, CSH can be estimated by the amount of CH, so the reduction of CH content caused by carbonization reaction also represents the reduction of CSH content, which is consistent with the phenomenon of reduction of CH and CSH in SEM.

[0095] In summary, the XRD analysis results show that the cement soil with biochar added contains a higher content of CH, which indicates that the addition of biochar can promote the formation of more hydration products in the cement soil at an early stage. In addition, the diffraction peak of CaCO3 in the cement soil sample with biochar added is more obvious, which suggests that the carbonization reaction is more thorough and the material structure is more compact, thereby improving the strength of the material. Due to its large micropore volume and specific surface area, biochar can not only provide effective channels and space for CO2 adsorption, but also create favorable conditions for the formation and growth of carbonization products. Therefore, the combination of biochar addition and carbonization curing process shows a significant synergistic effect.

[0096] (3.2) SEM test

[0097] Fig.14 The SEM images of CSBCS samples at 500 times and 5000 times magnification after standard curing for 28 days are shown. Fig.14 (a), (b), (c) and (d) show that the addition of CS-Biochar reduces the large gaps between soil particles in the CSBCS sample and makes the structure more compact. This trend becomes more obvious with the increase of CS-Biochar content. Fig.14 (c) It was found that biochar filled the spaces between soil particles and refined the internal voids of the sample, which is closely related to the strong hydrophilicity and ion exchange capacity of biochar itself. Fig.14 (e) and (f) show that the addition of CS-Biochar promotes the increase of CSH gel content, which is mainly wrapped on the surface of soil particles in the form of clouds and clusters, enhancing the bite force between particles. From a macroscopic point of view, the strength of the sample is increased and the structure is improved. At the same time, Fig.14 (f) shows that there is a small amount of CH in the sample in the form of thin flakes, and it is embedded between soil particles.

[0098] Fig.15 The SEM images of CSBCS samples at 500 times and 2000 times magnification after carbonization curing for 28 days are shown. Fig.15 (a), (b), (c) and (d) show that in the early stage of carbonation curing, irregular CaCO3 crystals are gathered on the surface of soil particles, making the sample structure more compact. Fig.15 (c) and (d) show that after carbonization of the CSBCS sample, the CaCO3 content increased significantly, mainly in the form of overlapping flakes, particle agglomeration and blocks. However, CSH and CH transformed into CaCO3 due to the carbonization reaction, resulting in a significant decrease in their content. Although CaCO3 can fill pores and reduce porosity, the transformation of CH and CSH to CaCO3 is related to volume expansion, which may cause soil debonding or microcracks, causing certain damage to the overall structure of the sample. Carbonization reaction and the addition of biochar increase the densification of the sample, but the generated CaCO3 adheres to the pore surface, which to a certain extent hinders the diffusion of CO2 into the soil, resulting in a decrease in the carbonization rate.

[0099] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization and curing technology, characterized in that: The following steps are involved: (1) Preparing an original composite material: mixing soft soil, cement, corn straw biochar, and water in a certain proportion to obtain an original composite material; (2) preparing modified cement soil: adding the original composite material into a mold in multiple times, compacting, and demolding to obtain modified cement soil; (3) Curing: The modified cement soil is subjected to carbonization curing to obtain negative carbon cement soil.

2. The method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization curing technology according to claim 1, characterized in that: The moisture content of the original composite material was 20%.

3. The method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization and curing technology according to claim 1, characterized in that: In the original composite material, cement accounts for 5% of the soft soil mass.

4. The method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization and curing technology according to claim 1, characterized in that: Corn stover biochar accounts for 3-7% of the total mass of cement and soft soil.

5. The method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization and curing technology according to claim 1, characterized in that: Before carbonization curing, the modified cement soil shall be subjected to standard curing or no standard curing; if no standard curing is carried out or the standard curing age is less than 7 days, the carbonization curing conditions are: temperature of 18-22°C, humidity of 70%, CO2 concentration of 50%, and carbonization time of 5-15 hours; if the standard curing age is greater than or equal to 7 days, the carbonization curing conditions are: temperature of 18-22°C, humidity of 70%, CO2 concentration of 50%, and carbonization time of less than or equal to 10 hours.

6. The method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization curing technology according to claim 5, characterized in that: Standard curing conditions are: temperature 18-22°C, humidity 95%.

7. The method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization and curing technology according to claim 1, characterized in that: The specific preparation steps of the original composite material are: after the soft soil and cement are mixed and stirred evenly, the corn straw biochar is poured in and stirred and mixed again, and then water is added and stirred and mixed again to obtain the original composite material.

8. The method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization and curing technology according to claim 1, characterized in that: When the negative carbon cement soil was prepared according to the conditions of 20% moisture content of the original composite material, 5% cement mass of soft soil, 3% corn straw biochar mass of cement and soft soil, and carbonization and curing for 15 hours at 18-22°C, 70% humidity, and 50% CO2 concentration, the CO2 absorption capacity of each ton of the negative carbon cement soil was 33.6kg; When negative carbon cement soil is prepared according to the conditions that the moisture content of the original composite material is 20%, cement accounts for 5% of the mass of soft soil, corn straw biochar accounts for 5% of the total mass of cement and soft soil, and carbonization curing is carried out for 15 hours at 18-22°C, humidity 70%, and CO2 concentration of 50%, the CO2 absorption capacity of each ton of the obtained negative carbon cement soil is 38.6kg.

9. The method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization and curing technology according to claim 1, characterized in that: The unconfined compressive strength UCS of the prepared negative carbon cement soil is calculated using the model z = α + βx 1.5 +λlny represents; z represents UCS, kPa; x represents biochar content, %; y represents curing age, h; α, β and λ are the unknown model fitting parameters.

10. The method for preparing negative carbon cement soil by using corn straw biochar synergistic carbonization and curing technology according to claim 9, characterized in that: The unconfined compressive strength of the negative carbon cement soil prepared under the conditions that the moisture content of the original composite material is 20%, the cement accounts for 5% of the soft soil mass, and the corn straw biochar accounts for 5% of the total mass of cement and soft soil and is carbonized and cured is higher than 2MPa. The unconfined compressive strength of the negative carbon cement soil prepared under the conditions that the moisture content of the original composite material is 20%, the cement accounts for 5% of the soft soil mass, and the corn straw biochar accounts for 7% of the total mass of cement and soft soil and is carbonized and cured is higher than 2MPa, which can meet the requirements of the subbase of expressways and first-class medium and light traffic roads, as well as second-class and below heavy, medium and light traffic highways.